Determinants of small-scale forestry practice preferences among landowners and land users in Imo State, Nigeria (2015)
Undertaking forestry practices on private land as a land use activities had been submitted to be mostly situational. There is a strong relationship between forestry and livelihood systems. This makes forestry practice a critical decimal in rural land use equation, most especially in tropical dry forest environment where soil nutrient is maintained by rich vegetation cover. But, in Southeastern Nigeria, the situations that can engender voluntary practice of forestry on private lands had not been thoroughly investigated. This paper therefore reports the findings of our investigation on such situation among land owners and users in Imo State, Nigeria. Multistage sampling technique was used in selecting 10% of the households across nine (9) randomly selected local communities in each of the three (3) geo-political districts of Imo State, Southeastern Nigeria. Using rapid rural appraisal technique, an estimated 5,091 households were documented across the selected nine communities out of which 509 were sampled. Data were collected with well-structured questionnaire, which formed the research instrument. The data were analyzed using descriptive statistics and multi-nomial logit regression. Highest preference was expressed by the respondents for raising fruit trees (71.2%) and planting trees with arable crops (60.3%) while lowest preference was for raising woodlot (23.9%). Males showed likelihood for planting medicinal herbs/shrubs (Coeff = 0.897) while females had likelihood for raising woodlot (Coeff = -0.402) within household lands. Within nuclear households, there is tendency for more household preference for planting timber tree species (Coeff = 0.136). This may be adduced to planting of trees within arable cropland to expectedly increase with increase in farm size. The reverse is however the case with raising woodlots on farm land (Coeff = -0.494). The higher energy needs of extended family may be responsible for this. These situations are therefore recommended to be built into planning and policy formulation premise to improve forestry practice for sustainable rural and national development.